High‐resolution digital elevation model from tri‐stereo Pleiades‐1 satellite imagery for lava flow volume estimates at Fogo Volcano - Marco Bagnardi; Pablo J. González; Andrew Hooper (Geophysical Research Letters)
Abstract Resolving changes in topography through time using accurate high‐resolution digital elevation models (DEMs) is key to understanding active volcanic processes. For the first time in a volcanic environment, we utilize very high‐resolution tri‐stereo optical imagery acquired by the Pleiades‐1 satellite constellation and generate a 1 m resolution DEM of Fogo Volcano, Cape Verde—the most active volcano in the Eastern Atlantic region. Point cloud density is increased by a factor of 6.5 compared to conventional stereo imagery, and the number of 1 m2 pixels with no height measurements is reduced by 43%. We use the DEM to quantify topographic changes associated with the 2014–2015 eruption at Fogo. Height differences between the posteruptive Pleiades‐1 DEM and the preeruptive topography from TanDEM‐X give a lava flow volume of 45.83 ± 0.02 × 106 m3, emplaced over an area of 4.8 km2 at a mean rate of 6.8 m3 s−1.